2007
DOI: 10.1002/pen.20868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clay on the morphology of poly(acrylonitrile‐butadiene‐styrene) and polypropylene nanocomposites

Abstract: The effects of clay on the morphology of the poly(acrylonitrile‐butadiene‐styrene) (ABS)/polypropylene (PP) nanocomposites were investigated. From the studies of wide angle X‐ray diffraction (WAXD) and transmission electron microscopy (TEM) analysis of the ABS/PP (70/30) nanocomposites with clay, it was observed that most of the clay existed in the ABS matrix because of the good affinity between the ABS and clay which contained benzyl group. From the studies of the scanning electron microscopy (SEM) analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Addition of block or graft copolymers as compatibilizer during processing helps in reducing interfacial tension and increasing interfacial adhesion through bridging or making entanglement between the polymers that improves the compatibility of the blends [17][18][19][20][21]. Many research groups [22][23][24][25][26][27][28][29][30] have reported nanoclay as a good compatibilizer in immiscible polymer blends over the past several years.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of block or graft copolymers as compatibilizer during processing helps in reducing interfacial tension and increasing interfacial adhesion through bridging or making entanglement between the polymers that improves the compatibility of the blends [17][18][19][20][21]. Many research groups [22][23][24][25][26][27][28][29][30] have reported nanoclay as a good compatibilizer in immiscible polymer blends over the past several years.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the breakup or elongated dispersed polymer phase droplets with the incorporation of filler reported in various research works [10,11] could also be the reason for the increase in η* of the blend composite system. Moreover, the morphological data of the present blend composite systems evidenced the entrapped NFA particles at the blend interface that can also be ascribed to the increased η* of the composite systems as compared with neat PP/ABS blend.…”
Section: Complex Viscositymentioning
confidence: 95%
“…Similar kind of observation has also been reported by Gcwabaza et al [11] in study of PP/PBS/ C20A blend nanocomposites. However, Sung et al [10] also reported that in case of any compatibilization effect of filler in the blend system, a possible shift of tan δ peak value is expected. Similar facts, i.e., the shift in tan δ peaks of NFA filled PP/ABS blend composites, have been observed in the present study which supports the compatibilization effect of NFA within PP/ABS blend matrix phases.…”
Section: Storage Modulusmentioning
confidence: 95%
See 2 more Smart Citations